A high-precision40Ar/39Ar age for the Nrdlinger Ries impact crater, Germany, and implications for the accurate dating of terrestrial impact events - Schmieder, M.; Kennedy, T.; Jourdan, Fred; Buchner, E.; Reimold, W. (Pergamon, 2018)
© 2017 Elsevier Ltd 40 Ar/ 39 Ar dating of specimens of moldavite, the formation of which is linked to the Ries impact in southern Germany, with a latest-generation ARGUS VI multi-collector mass spectrometer yielded three fully concordant plateau ages with a weighted mean age of 14.808 ± 0.021 Ma (± 0.038 Ma including all external uncertainties; 2s MSWD = 0.40, P = 0.67). This new best-estimate age for the Nördlinger Ries is in general agreement with previous 40 Ar/ 39 Ar results for moldavites, but constitutes a significantly improved precision with respect to the formation age of the distal Ries-produced tektites. Separates of impact glass from proximal Ries ejecta (suevite glass from three different surface outcrops) and partially melted feldspar particles from impact melt rock of the SUBO 18 Enkingen drill core failed to produce meaningful ages. These glasses show evidence for excess 40 Ar introduction, which may have been incurred during interaction with hydrothermal fluids. Only partially reset 40 Ar/ 39 Ar ages could be determined for the feldspathic melt separates from the Enkingen core. The new 40 Ar/ 39 Ar results for the Ries impact structure constrain the duration of crater cooling, during the prevailing hydrothermal activity, to locally at least ~60 kyr. With respect to the dating of terrestrial impact events, this paper briefly discusses a number of potential issues and effects that may be the cause for seemingly precise, but on a kyr-scale inaccurate, impact ages.